Subsite variation of HPV-related p16-expression in oropharynx cancer: Incidence and prognostic impact in a population-based DAHANCA cohort 1986–2020 - Pernille Lassen; Jan Alsner; Hanne Primdahl; Christina Caroline Plaschke; Christian Maare; Jørgen Johansen; Maria Andersen; Mohammad Farhadi; Jens Overgaard (Acta Oncologica)
p16-expression are implemented in the TNM8 classification of oropharyngeal cancer (OPSCC). Based on a nationwide cohort, we provide a detailed description of subsite variation in the age-standardised incidence-rates of OPSCC alongside an evaluation of the prognostic impact of p16-expression according to subsite after primary radiotherapy (RT).